THE IMPACT OF FOOD LAW POLICIES ON LOCAL COMMUNITY EMPOWERMENT IN INDONESIA’S SUSTAINABLE FOOD GARDEN PROGRAM - Widyastuti, Tiyas Vika; Hamzani, Achmad Irwan; Masdurohatun, Anis (Indonesia Law Review, 2024)
This research examines the impact of food law politics on community empowerment and sustainable agriculture in Indonesia, focusing on the Sustainable Food Garden Program (P2L). Utilizing a normative juridical analysis, it explores how legal frameworks can support or obstruct community-led agricultural initiatives. The study highlights the empowering effect of laws aligned with community goals and the challenges arising from legislation favoring industrial agriculture. It proposes legal reforms to address ambiguities and barriers, such as clarifying land tenure rights and simplifying organic certification processes. Recommendations aim to foster a legal environment conducive to sustainable, community-driven agriculture, enhancing food security and environmental sustainability. This paper contributes insights into legal and policy reforms needed to empower communities and promote sustainable agricultural practices in Indonesia.